AN ANALYSIS OF READING MATERIAL IN ENGLISH IN FOCUS TEXTBOOK FOR GRADE XSENIOR HIGH SCHOOL PUBLISHED BY DEPARTMENT OF NATIONAL EDUCATION (RETAIN, 2016)
AN ANALYSIS OF READING MATERIAL IN ENGLISH IN FOCUS TEXTBOOK FOR GRADE XSENIOR HIGH SCHOOL PUBLISHED BY DEPARTMENT OF NATIONAL EDUCATION KHIBBAN NURCAHYO English Education, Language and Art Faculty, State University of Surabaya ibannurcahyi@gmail.com Drs. FAHRI, M.A., fahri@unesa.ac.id English Education, Language and Art Faculty, State University of Surabaya Abstrak Zamanini Bahasa Inggris memiliki peran yang sangat penting dan posisi di era globalisasi. Hal ini sangat penting untuk pengembangan pengetahuan, ilmu pengetahuan, budaya dan hubungan antara negara-negara. Target belajar bahasa Inggris di SMA menggunakan fungsional dan menggunakan tingkat, itu berarti bahwa dengan belajar bahasa Inggris di SMA (SekolahMenengahAtas) , siswa dapat berkomunikasi dalam bahasa Inggris apakah lisan atau tertulis dalam kehidupan sehari-hari mereka. Salah satu cara untuk dapat berkomunikasi digunakan membaca. Membaca adalah salah satu keterampilan dalam bahasa Inggris yang harus dikuasai oleh siswa ketika mereka belajar bahasa Inggris. Karena itu, siswa harus belajar membaca serta keterampilan lain jika mereka ingin menguasai bahasa Inggris. Menurut Nunan (2003: 68) "Membaca adalah proses fasih mana dalam membangun makna, pembaca harus menggabungkan informasi dari teks dengan latar belakang mereka sendiri pengetahuan". Dan dalam membaca ada beberapa bahan. Untuk mempelajari materi bahasa Inggris, siswa membutuhkan bimbingan atau alat-alat yang membantu mereka untuk memahami dengan baik. Dalam pendidikan formal, buku ini sangat penting dan banyak digunakan oleh guru dan siswa ketika mereka belajar materi bahasa Inggris. Guru harus selektif dalam menggunakan buku teks yang akan digunakan untuk mengajar membaca.Untuk membuat siswa mampu mencapai materi bahasa Inggris, mereka membutuhkan beberapa buku pelajaran bahasa Inggris yang memiliki kualitas yang baik. Dengan belajar mereka buku pelajaran yang memenuhi syarat, mereka mampu meningkatkan produktivitas keterampilan bahasa Inggris mereka. Berurusan dengan kualitas buku teks, pada 2013 Departemen Pendidikan Nasional menerbitkan beberapa BSE (Buku Sekolah Elektronik) buku teks bahasa Inggris. Salah satunya adalah buku teks bahasa Inggris untuk kelas sepuluh SMA berjudul English in Focus yang tidak hanya digunakan oleh sekolah-sekolah umum tetapi juga sekolah swasta. Berdasarkan latar belakang belajar di atas, peneliti melakukan studi untuk melihat apakah bahasa Inggris dalam buku fokus dapat memenuhi aspek dari buku teks bahasa Inggris yang berkualitas. Khusus untuk kelas satu SMA. Dengan mempelajari buku teks ini, peneliti menggunakan analisis dokumen, di sini di semester pertama kita memenuhi beberapa aspek. Mereka adalah (1) aspek konten, (2) aspek presentasi, (3) penggunaan aspek dan mudah dibaca. Kata kunci: analisis, buku, Reading, Aspek konten, SMA (Sekolah Menengah Atas) Abstract Reading is one of the skills in English that has to be mastered by the students when they are learning English. Because of that, students have to learn reading as well as the other skills if they want to master English..To learn English material, the student need guidance or tools that help them to comprehend it well.To make students be able to achieve the English materials, they need some English textbooks which have good quality. Dealing with the quality of a textbook, in 2013 Department of National Education publishes some BSE (BukuSekolahElektronik) English textbooks. One of them is an English textbook for tenth Grade of Senior High School entitled “English in Focus” which is not only used by public schools but also private schools.Based on the background of the studying above, the researcher conducts the study to see whether English in focus textbook can meet the aspect of a quality English textbook. Especially for first grade of senior high school.here in the first semester we meet the some aspects. They are (1) aspect of content, (2) aspect of presentation, (3) aspect use and readability.The researcher used the triangulation technique to gain the validity of the data. Burns (1999: 169) said that triangulation is one of the most commonly techniques used and known ways of checking for validity. The goal of triangulation is to gather multiple perspectives on the situation being studied. There are four types of triangualition; they are by source, by method, by observers, and by theories. The researcher used theory triangulation and observer triangulation in this research. Besides the triangulation by theory, the researcher also triangulated the data observer. The data from textbook were re-typed. They were used to triangulate the data. This research was also consulted to the consultant in order to confirm the data. The researcher confirmed the research to his thesis supervisor.The reading materials were analyzed based on aspect of contents. The conclusion is regarding to the contents of the English inFocus textbook. Dealing with aspect of contents of the textbook, there are some points toanalyze. Those points are the conformity between reading materials andcurriculum, kind of genres found in the reading materials, the arrangement ofreading materials based on the level of difficulty, reading tasks which are given todevelop students’ ability, the reading materials which are supporting life skills andthe reading materials which consider the aspects of gender, religion and race.Actually, almost all the points of aspect of contents had already fulfilled by English in Focus textbook, except the conformity between reading materials andcurriculum since there are some reading indicators that cannot be found in thereading materials. Key words: an analysis ,textbook , Reading, Aspect of content, Senior High School